Investigation and Histopathological Evaluation of the Effects of Omeprazole on the Ischemia-Reperfusion Induced Oxidative Damage and DNA Mutation in Rat Ovarian Tissue - Demiryilmaz, Ismail; Cetin, Nihal; Erkan Yapca, Omer; Altuner, Durdu; Isaoglu, Unal; Betul Ozgeris, Fatma; Calik, Muhammet; Suleyman, Halis (Asian Journal of Chemistry, 2013)
In this study, the biochemical and histopathological effects of omeprazole on ischemia-reperfusion (I/R) induced oxidative damage in rat ovarian tissue were investigated. The moment that the animals remained motionless in supine position was considered the appropriate time to perform surgery. The ovaries of the rats were reached through a 2.0-2.5 cm long vertical incision in the lower abdomen. Subsequently, in the omeprazole (OIR) and the control groups (I/RC), a vascular clip was placed in the lower part of the right ovary (the part where the ovary is attached to the uterus) and ischemia was maintained for 3 h. (No ischemia was applied in the healthy group.) After this period, the vascular clip was removed in order to provide reperfusion for 2 h. Afterwards, all the animals were terminated by high dose-anesthesia, the ovaries were removed and histopathological and biochemical studies were performed. Omeprazole has an antioxidant effect and it can have a protective function in the oxidative damage induced by ischemia-reperfusion. We have found that omeprazole prevents oxidative damage due to ischemia-reperfusion injury in rat ovarian tissue.